Play Therapy for Strengthening Child Attachment through Communication in Children with Autism Spectrum Disorder (ASD) at SLB X - Wiliam Filix Zadok; Yuspendi Yuspendi; Ria Wardani (Green Publisher Indonesia, 2025)
This study aims to describe the effectiveness of play therapy in strengthening child attachment through communication in children with Autism Spectrum Disorder (ASD) at a Special Needs School (SLB) X. The main issue addressed is the difficulty children with ASD face in forming emotional bonds with their parents due to barriers in social communication. This research employs a quantitative approach with a one-group pretest-posttest quasi-experimental design, involving five boys aged 6–12 years who have been diagnosed with ASD. The intervention consisted of communication-based play therapy sessions that actively involved parents in joint play activities with their children. Attachment was measured using the Attachment Q-Sort (AQS) tool, which covers three dimensions: secure, resistant, and avoidant attachment. Data analysis using the Paired Sample T-Test showed a significant increase in the secure attachment dimension, while changes in resistant and avoidant attachment were not significant. These findings indicate that play therapy emphasizing verbal and non-verbal communication is effective in enhancing secure attachment between parents and children with ASD, highlighting the importance of active parental involvement in fostering warm, responsive interactions that support the child’s social-emotional development.